2008
DOI: 10.1017/s0024282908007664
|View full text |Cite
|
Sign up to set email alerts
|

Epiphytic lichen biomass in a boreal Norway spruce forest

Abstract: Abstract:Alectorioid and foliose lichens were weighed from full-size branches of Picea abies cut at two canopy heights in 100 trees in an old subalpine forested area in eastern Norway. The mean lichen biomass per branch decreased from 46 to 37 g moving upwards from 2–3 to 5–6 m canopy height. The lichen biomass correlated strongly with branch size variables, branch diameter alone explaining 48 of the variation in lichen biomass per branch (n=200). The alectorioid/foliose biomass ratio increased from 0·149 at 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 38 publications
(53 reference statements)
2
24
0
Order By: Relevance
“…1b) and/or Usnea on lower, often defoliated branches (Campbell and Coxson 2001, Benson and Coxson 2002, Coxson and Coyle 2003. In Norwegian boreal forests, the biomass of Bryoria increased by a factor of 1.6 from 2-3 m to 5-6 m above the ground, with a concurrent decline (to 61%) in Alectoria and Usnea (Gauslaa et al 2008); their sites are in the same bioclimatic region as our Norwegian site. The mechanism behind this niche partitioning is poorly understood, but various factors are apparently involved.…”
Section: Introductionmentioning
confidence: 59%
“…1b) and/or Usnea on lower, often defoliated branches (Campbell and Coxson 2001, Benson and Coxson 2002, Coxson and Coyle 2003. In Norwegian boreal forests, the biomass of Bryoria increased by a factor of 1.6 from 2-3 m to 5-6 m above the ground, with a concurrent decline (to 61%) in Alectoria and Usnea (Gauslaa et al 2008); their sites are in the same bioclimatic region as our Norwegian site. The mechanism behind this niche partitioning is poorly understood, but various factors are apparently involved.…”
Section: Introductionmentioning
confidence: 59%
“…Forests at the forest-steppe ecotone at the southern fringe of the central Siberian taiga, however, show a gradient where the trees at the highly sun-exposed forest line to the steppe are inhabited by epiphytes producing effective sunscreens, including usnic acid and melanins, whereas lichens with less efficient photoprotection, including atranorin-containing species, increase with increasing distance from the forest edge . Gauslaa et al (2008) discussed the possibility that the vertical zonation of alectorioid lichens within the canopy of boreal forests might be due to differences in the light-screening efficiency of cortical pigments between different genera (usnic acid in Alectoria and Usnea versus melanins in Bryoria).…”
Section: Lightmentioning
confidence: 99%
“…A previous study found relationships between lichen growth and site factors reflecting the openness o f the canopy (Gauslaa et al, 2008). In that study, main branches were cut down from two height intervals on each tree to quantify epiphytic lichen biomass.…”
Section: Functional Group Nitrogen Contentmentioning
confidence: 99%
“…There are microclimatic gradients in moisture, temperature, light, and nutrient availability, all which could be influencing the growth of certain types of lichen functional groups at a certain height (Gaio-Oliveira et al, 2004;Gauslaa et al, 2007). Branch length measurements could have been taken, as branch size is an important predictor for epiphytic lichen biomass (Gauslaa et al, 2008). Finally, forest structure, age, site conditions, weather 52 patterns, disturbance regimes, and ground species composition may also be determining factors for epiphytic lichen biomass presence and abundance (Pipp et al, 2001).…”
Section: Functional Group Nitrogen Contentmentioning
confidence: 99%
See 1 more Smart Citation